Transport and expression of transporters for 3-O-methyl-D-glucose and L-methionine along the intestine of broiler chickens receiving different methionine supplements - Julia Riedel; Isabel I. Schermuly; Stella Romanet; Eva-Maria Saliu; Andreas Lemme; Jürgen Zentek; Jörg R. Aschenbach (Poultry Science)
The present study hypothesized that supplementation of different methionine (Met) sources might influence the intestinal absorption of L-Met and 3-O-methyl-D-glucose (3-OMG) in broilers. In a completely randomized study, a total of 53 Cobb500 broilers (30 males and 23 females) received a grower-finisher diet that was either not supplemented with Met (Met + Cys, 0.49 %; control) or supplemented with either 0.27 % L-Met, 0.27 % DL-Met or 0.47 % DL-2‑hydroxy-4-(methylthio) butanoic acid (HMTBA). After ≥10 days on the diets, uptakes of 3-OMG and L-Met were measured in duodenum, mid-jejunum and caecum at 50 µM and 5 mM concentrations in Ussing chambers, each in the presence and absence of Na+. We also investigated the mRNA expression of apical glucose and Met transporters. Dietary supplements had no effect on 3-OMG and L-Met uptakes (P > 0.05), except for male broilers receiving DL-Met or DL-HMTBA, that showed higher jejunal uptakes of L-Met than control at 5 mM (P < 0.001). Except for L-Met uptakes at 5 mM, tissue × sodium interactions (P ≤ 0.05) for 3-OMG and L-Met uptakes verified higher uptakes in jejunum compared to duodenum and caecum; with higher uptakes in the presence vs. absence of Na+ in jejunum only. In duodenum, uptakes of L-Met and 3-OMG at 50 µM concentration were higher in males vs. females. Expression of SGLT1, B0AT1, ATB0,+ and rBAT, but not ASCT1, were lowest in caecum (P ≤ 0.05). Expression of B0AT1 was higher in males vs. females (P ≤ 0.05). Expression of ASCT1 was higher with DL-Met and DL-HMTBA supplements compared to L-Met and control (P ≤ 0.05). These findings indicate that jejunum is the main intestinal segment for Na+-dependent L-Met and 3-OMG absorption in broilers with minor effects of dietary Met source. A sexual dimorphism for duodenal nutrient uptake and mRNA abundance of B0AT1 was congruent with the more efficient growth performance of male chickens known from the literature.